Evaluating Public Parks as Walkable Places towards Achieving Livable Cities. - Al-Obeidy, Musaab Sami (Sulaimani Journal for Engineering Sciences, 2017)
In ancient times, walking was the first mode of transportation that human used, where humans walked on the earth in search of food, water, and shelter. Nowadays following many decades of development, the nature of mankind has changed due to a change in their needs and lifestyle, which includes the emergence and development of transportation modes, such as cars, buses, and trains. Modes of travel from place to place have changed, whereas reliance on using cars in travel is increasing. The problem of the study is increasing the use of cars and depending on them as a major mean of transportation instead of walking on foot. Hence, the concept of walkability is manifested, and is defined as the extent to which walking is readily available to the pedestrian as a safe, connected, accessible, and pleasant activity. Through this definition, this research examines or evaluates factors of walkability in National Park in Kuala-Lumpur through studying and analyzing dependent travel mode and behavior of its users. The Kuala Lumpur City was chosen as the case study based on being the capital of Malaysia and the only city being included in the Annual World Ranking of the Most Livable Cities in Malaysia. The aim of this study is to diagnose factors that have an impact on walkability, thus supporting travel by foot, using public transportation and bicycle, and reducing the usage of cars. All of these issues are to make Kuala-Lumpur as a more livable city and within top 20 livable cities in the world in 2020. The methodology of research depends on two types of techniques: quantitative as the main technique by applying 240 questionnaire surveys; and the qualitative technique in support of the first technique by applying 20 interviews, as well as direct observation of the location. This study concludes that it is difficult to reduce dependency on cars as mode of moving from place to other, since there is a lack in providing comfort and safety, which affects other factors of walkability. Thus, listing Kuala-Lumpur within the best 20 livable cities in the world as 2020 plan will be more difficult.
Keywords: Walkability; Livable Cities; Public Parks